1997
DOI: 10.1002/hep.510250344
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Genotypes and Risk of Hepatocellular Carcinoma in Cirrhosis: A Prospective Study

Abstract: approximately 3%. 3,4 Early detection of HCC in cirrhotic pa-A prospective study was performed to establish tients can usually be achieved by screening with noninvasive whether infection with specific hepatitis C virus (HCV) techniques, such as ultrasound (US) scan and serum a-fetogenotypes was associated with an increased risk of protein (AFP) concentration. 5,6 development of hepatocellular carcinoma (HCC) in cirOver the years, several lines of experimental evidence indirhosis. A cohort of 163 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
6
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(210 citation statements)
references
References 40 publications
7
193
6
4
Order By: Relevance
“…Age could also explain the lower rate of complications, only 2%, that was evident among the 198 patients who acquired HCV from IDU, a finding consistent with the observations of Gordon et al 22 In this and other studies, 13,28 gender had no effect on liver-related complications other than the development of HCC, which as observed in many diseases is more common in men. [35][36][37][38] In this study, HCV acquired from BT and cases without identified risk factors (sporadic cases) were at higher risk of liver-related complications compared with IDU cases. However, only ''sporadic'' was an independent predictor of liverrelated complications.…”
Section: Discussionmentioning
confidence: 68%
“…Age could also explain the lower rate of complications, only 2%, that was evident among the 198 patients who acquired HCV from IDU, a finding consistent with the observations of Gordon et al 22 In this and other studies, 13,28 gender had no effect on liver-related complications other than the development of HCC, which as observed in many diseases is more common in men. [35][36][37][38] In this study, HCV acquired from BT and cases without identified risk factors (sporadic cases) were at higher risk of liver-related complications compared with IDU cases. However, only ''sporadic'' was an independent predictor of liverrelated complications.…”
Section: Discussionmentioning
confidence: 68%
“…The need for closer monitoring of patients with chronic hepatitis who have a high risk of developing HCC during the course of the disease 19 has long been stated. In these patients, sAFP has been a particularly unsatisfactory screening tool for early detection of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Using an antiphospho-Erk1/2 MAP Kinases antibody (New England Biolabs), that speci®cally recognizes activated Erk1/ Erk2, we showed that HCV core type 1 activates endogenous ERKs (Figure 1a, top panel, lane 3), whereas the pCDNA3-HA empty vector and the pCDNA3-GFP expression vector (Figure 1a, top panel, lanes 1 and 2) have no e ect. Although it has been proposed that HCV genotypes may have a di erent impact on the natural history of the infection and on the risk of HCC development (Bruno et al, 1997) we observed that type 3 HCV core activates at the same extent endogenous Erk1/2 ( Figure 1a, top panel, lane 4).…”
mentioning
confidence: 61%